Western Europe 2026 - Ham, Anthony (Lonely Planet guidebooks., 2026)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to Western Europe. Discover Western Europe's most popular experiences and best kept secrets from relaxing on white Mediterranean sand beaches lapped by turquoise waters, to skiing down majestic snow-capped mountain ranges, and exploring a cache of world-famous museums and art galleries. Build a trip to remember with Lonely Planet's Western Europe travel guide: Our classic guidebook format contains the most comprehensive level of information for planning multi-week trips All-new structure and design that's easy to use so you can navigate Western Europe effortlessly Exciting itineraries help you create your perfect adventure with suggestions for extended journeys, day trips, walking tours and activity-led excursions Expert local recommendations on eating, drinking, nightlife, shopping, accommodation, festivals, when to go and more Vibrant photography and maps Get fresh takes on must-visit sights from the Eiffel Tower to La Sagrada Família and Edinburgh Castle Essential information toolkit containing tips on arriving; transport; local etiquette; using money; LGBTIQ+ travel advice; useful words and phrases; accessibility; and responsible travel Connect with Western European culture through stories that delve deep into local life, history and traditions Covers: Austria, Belgium & Luxembourg, Britain, France, Germany, Greece, Ireland, Italy, The Netherlands, Portugal, Spain, Switzerland Create a trip that's uniquely yours and get to the heart of this extraordinary part of the world with Lonely Planet's Western Europe.